Mycobacterium tuberculosis Infection-Driven Foamy Macrophages and Their Implications in Tuberculosis Control as Targets for Host-Directed Therapy - Shim, Dahee; Kim, Hagyu; Shin, Sung Jae (Frontiers in Immunology, 2020)
Tuberculosis (TB) is a leading cause of death worldwide following infection with Mycobacterium tuberculosis (Mtb), with 1.5 million deaths from this disease reported in 2018. Once the bacilli are inhaled, alveolar and interstitial macrophages become infected with Mtb and differentiate into lipid-laden foamy macrophages leading to lung inflammation. Thus, the presence of lipid-laden foamy macrophages is the hallmark of TB granuloma; these Mtb-infected foamy macrophages are the major niche for Mtb survival. The fate of TB pathogenesis is likely determined by the altered function of Mtb-infected macrophages, which initiate and mediate TB-related lung inflammation. As Mtb-infected foamy macrophages play central roles in the pathogenesis of Mtb, they may be important in the development of host-directed therapy against TB. Here, we summarize and discuss the current understanding of the alterations in alveolar and interstitial macrophages in the regulation of Mtb infection-induced immune responses. Metabolic reprogramming of lipid-laden foamy macrophages following Mtb infection or virulence factors are also summarized. Furthermore, we review the therapeutic interventions targeting immune responses and metabolic pathways, from in vitro, in vivo, and clinical studies. This review will further our understanding of the Mtb-infected foamy macrophages, which are both the major Mtb niche and therapeutic targets against TB.